UNVEILING STRATEGIES FOR SHORTENING TUBERCULOSIS TREATMENT: TARGETING MYCOBACTERIUM TUBERCULOSIS STRINGENT RESPONSE AND REVIEWING POLYPHOSPHATE KINASE 2 (PPK2) ENZYMES - SINGIRISETTY TRIVENI; KURUBA VIJAYA BHASKAR; CHILAMAKURU NARESH BABU; MALLELA VIJAYA JYOTHI (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Tuberculosis (TB) is one of the oldest infectious diseases known to humankind, with traces of its presence found in remains that are around 17,000 years old. TB is mostly caused by the tiny aerobic non-motile bacillus Mycobacterium TB (MTB). The unique shape and chemical content of the mycobacterial cell wall make an efficient TB therapy method challenging. A strict bacterial survival strategy for establishing drug tolerance in the stringent response (SR), MTB is a sophisticated remodeling of metabolism that slows down growth and energy requirements during famine. Recent studies emphasize the need to focus on the SR in MTB as a means of reducing the treatment duration. The MTB genome codes two polyphosphate kinases (PPK-1 and PPK-2), for maintenance of intracellular Inorganic Polyphosphate (Poly P) levels. The identification of a virulence factor of TB growth as well as persistence in host tissues may be helped in MTB using PPK2, which is required to modulate intracellular levels of regulating molecules and to sustain sensitivity to the first-line anti-drug isoniazid. Synthesized and under control by PPK2 enzymes, inorganic polyP is essential in this process since it controls stress reactions. This research, therefore, investigates the significance of PPK2 in the MTB, the chemicals suppressing a bacterial SR in MTB, and the list of PPK2 inhibitors for shortening TB.